2009
DOI: 10.1177/0961203309346975
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of healthy subjects and autoantibodies: from mice through dogs to humans

Abstract: Vaccination against pathogenic microorganisms is one of the major achievements of modern medicine, but due to an increasing number of reports of adverse reactions the vaccination procedure has induced also considerable debate. It is well known that certain infections are involved in triggering the production of autoantibodies, which could lead to autoimmune adverse reactions in genetically predisposed subjects. Based on these findings it was assumed that vaccinations might induce similar autoimmune reactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Although there was no statistically significant production of aPL after vaccination with hepatitis B vaccine in healthy adults, a long-term aPL response in genetically predisposed individuals could not be excluded. [25][26][27] In another study, low rate of aCL positivity was demonstrated in healthy individuals 3 months after influenza vaccination. 28 Thus, we suggest that susceptible individuals (genetically prone) have an increased risk of developing a sustained autoimmune response, and subsequently produce autoantibodies after vaccination or exposure to adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no statistically significant production of aPL after vaccination with hepatitis B vaccine in healthy adults, a long-term aPL response in genetically predisposed individuals could not be excluded. [25][26][27] In another study, low rate of aCL positivity was demonstrated in healthy individuals 3 months after influenza vaccination. 28 Thus, we suggest that susceptible individuals (genetically prone) have an increased risk of developing a sustained autoimmune response, and subsequently produce autoantibodies after vaccination or exposure to adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…Manifestations of APS 1 in the mouse model include a decrease in fecundity and/or fertility. Various data that connect exposure to microbial antigens, either during infections [2][3][4][5] or vaccinations, [6][7][8][9][10] to autoantibody production have been published in recent years. Experimental evidence for infectious origins of APS came from mice, immunized with a panel of microbial preparations, which developed anti-b 2 GPI Abs.…”
Section: Introductionmentioning
confidence: 99%
“…Such reactions are usually rare and transient. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Quadrivalent human papilloma virus (qHPV) types 6, 11, 16 and 19 recombinant vaccine has been approved for young women for prevention of cervical cancer, showing 90-100% efficacy in the prevention of precancerous cervical, vaginal and vulvar lesions and genital warts. Reported serious adverse events include Guillain-Barre´syndrome (GBS), transverse myelitis, pancreatitis, venous thromboembolism (VTE), and 51 cases of autoimmune diseases, including SLE in 18, RA in 13, mixed connective tissue disease in four, and Sjogren's, dermatomyositis, and scleroderma in one patient each.…”
Section: Discussionmentioning
confidence: 99%